"Oni". Analiza medijskega diskurza: Mladina in spletni forumi - Markovčič, Ines (Monitor ISH, 2004)
'Them'. An analysis of media discourse: Mladina and on-line forums. The paper presents a critical and linguistic analysis of certain major discourse structures used by the Slovene media to establish a negative, intolerant, and exclusive attitude to the ethnic minorities from the former Yugoslav republics. The presentation is based on our study of Mladina, a Slovene political weekly, and its on-line discussion groups. Drawing upon linguistic representations in print and on-line discourse, we attempt to show that all meanings expressed by mass communication texts are social constructs and that every kind of discourse is a social practice, through which ideological and intolerant representations of ethnicity are reproduced. Obviously, the ethics of journalistic discourse will have to be addressed in the future more than once.
Keywords: Slovenia; Slovenija; množični mediji; mass media; Mladina (periodična publikacija); etnične manjšine; novinarski diskurz; spletni forumi; sovražni govor; ksenofobija